Integrated sustainable farming model for saline and sodic soils - Rajkumar; Kumar, Suresh; Fagodia, Ram Kishor; Singh, Awtar; Singh, Nirmal (Indian Farming, 2025)
Saline and sodic soils significantly limit agricultural productivity due to their high salt and sodium content, which negatively affect soil health and crop growth. This article explores the effectiveness of integrated sustainable farming systems (IFS) in mitigating these challenges and enhancing farm productivity in affected regions. By combining crop diversification, efficient water management, livestock integration, and agroforestry, IFS promotes resource recycling, improves soil fertility, and maintains ecological balance. The adoption of these holistic practices results in enhanced biodiversity, climate resilience, and economic sustainability for smallholder farmers. Case studies from the Indo-Gangetic Plains highlight that enterprise diversification within IFS increases food and nutritional security, reduces environmental degradation, and boosts farm profitability. Despite challenges like limited funding and resource availability, integrated farming presents a viable solution for sustainable agriculture on saline and sodic soils, supporting both farmer livelihoods and long-term soil conservation.